ANALISIS YURIDIS TINDAK PIDANA PERDAGANGAN ORANG DALAM ERA TRANSFORMASI TEKNOLOGI INFORMASI DAN KOMUNIKASI UNTUK MEWUJUDKAN PERLINDUNGAN HUKUM (STUDI KASUS DIREKTORAT RESERSE KRIMINAL UMUM KEPOLISIAN DAERAH KEPULAUAN RIAU) - Ayuniawati Ayuniawati; Fadlan Fadlan; Juhrin Pasaribu (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
The problem of trafficking in persons has recently emerged as a much debated issue both at the regional and global levels and is caused by a form of slavery. The author is interested in choosing this title topic because this problem occurs a lot at this time, this has a big impact if left unchecked. This study aims to (1) find out the legal arrangements for the criminal act of trafficking in warlocks in the Riau Archipelago Province. (2) To find out what are the obstacle factors and solutions in the implementation at the time of the investigation regarding the criminal case of trafficking in persons in the Riau Islands Province. This study uses a normative legal method that aims to find a truth. This research was conducted at the Directorate General of Criminal Investigation of the Riau Islands Regional Police with sample data provided by the Riau Islands Police regarding the investigation of criminal acts of trafficking in persons. The results of this study are (1) Against the suspect Sdra AKUI als AWI, the elements of the alleged article have been fulfilled including recruiting, sending, receiving, fraud, sheltering, debt bondage, receiving benefits, and abusing vulnerable positions with the aim of sexually exploiting victims. and economics and intentionally making as a livelihood or as a habit of doing or facilitating acts of violating decency by other people to third persons and committing, ordering to do and participating in committing such criminal acts as regulated in the formulation of Article 2 of the Law of the Republic of Indonesia Number 21 of 2007 concerning Trafficking in Persons and Article 296 in conjunction with Article 55 paragraph (1) to (1) of the Criminal Code. (2) Economic factors/poverty, education factors, environmental factors, and other factors are factors that cause trafficking in persons. With this case, it is better to form a task force that involves many members with sub-groups and involves the community. Keywords: Trafficking in Persons, Legal Protection, Crime, ICT.